Legal Construction of Immigration Administrative Measures: A Case Study on Immigratoir, Asylum Seekers, and Refugees - Muhammad Yani Firdaus (Reformasi Hukum, 2025)
Indonesia, as an archipelagic state located at the crossroads of global routes, faces dynamic human mobility, including immigratoir, asylum seekers, and refugees. This study aims to examine the legal construction of immigration administrative actions in Indonesia and their implications for sovereignty and national immigration policy. The research applies a qualitative method with a normative juridical approach based on literature review and regulatory analysis. The findings show that national regulations do not fully reflect the principle of lex superior derogat legi inferior. Although Indonesia has not ratified the 1951 Refugee Convention and the 1967 Protocol, it still bears responsibility for managing asylum seekers and refugees, creating regulatory and operational challenges. The study concludes that the role of the Directorate General of Immigration must be reinforced through cross-sectoral coordination with the military, police, local governments, and related stakeholders. Recommendations highlight three priorities: revising Presidential Regulation No. 125 of 2016 to align with national interests, requiring UNHCR to consult the Indonesian government before granting refugee status, and ensuring financial and logistical responsibilities are borne by IOM to prevent excessive burdens on Indonesia.